An ecological perspective on water shedding from leaves. (2nd November 2021) - Lenz, Anne-Kristin; Bauer, Ulrike; Ruxton, Graeme D
Abstract : The complex interaction between rain, vegetation, soil, and climate can only be understood by studying form–function relationships of leaves in a meaningful ecological context. Abstract: Water shedding from leaves is a complex process depending on multiple leaf traits interacting with rain, wind, and air humidity, and with the entire plant and surrounding vegetation. Here, we synthesize current knowledge of the physics of water shedding with implications for plant physiology and ecology. We argue that the drop retention angle is a more meaningful parameter to characterize the water-shedding capacity of leaves than the commonly measured static contact angle. The understanding of the mechanics of water shedding is largely derived from laboratory experiments on artificial rather than natural surfaces, often on individual aspects such as surface wettability or drop impacts. In contrast, field studies attempting to identify the adaptive value of leaf traits linked to water shedding are largely correlative in nature, with inconclusive results. We make a strong case for taking the hypothesis-driven experimental approach of biomechanical laboratory studies into a real-world field setting to gain a comprehensive understanding of leaf water shedding in a whole-plant ecological and evolutionary context.